Native soil microorganisms hinder the soil enrichment with antibiotic resistance genes following manure applications - Pérez-Valera, Eduardo (Sci Rep, 2019)
Bacterial genes responsible for resistance to antibiotic agents (ARG) are spread from livestock to soil through application of manure, threatening environmental and human health. We investigated the mechanisms of ARG dissemination and persistence to disentangle i) the influence of nutrients and microorganisms on the soil tetracycline (TET) resistome, and ii) the role of indigenous soil microbiota in preventing ARG spread. We analysed short-term (7 days) and persistent (84 days) effects of manure on the resistome of three antibiotic-free pasture soils. Four microcosm treatments were evaluated: control, mineral nutrient fertilization, and deposition of a layer of fresh manure onto soil or γ-irradiated soil. We quantified five TET-resistance genes, isolated 135 TET-resistant bacteria and sequenced both culturable TET-resistant and whole bacterial communities. Manure amendments, but not nutrient addition, increased the abundance of TET-r genes such as tet(Y). Such changes persisted with time, in contrast with the TET-resistant bacterial composition, which partially recovered after manure amendments. Manured γ-irradiated soils showed significantly lower nutrient content and higher TET-r gene abundance than non-irradiated soils, suggesting that native soil bacteria are essential for the fertilization effect of manure on soil as well as control the dissemination of potentially risky TET-r genes.